Attempts to optimize postinduction treatment in childhood acute myeloid leukemia without core‐binding factors: A report from the Japanese Pediatric Leukemia/Lymphoma Study Group (JPLSG). Issue 12 (4th September 2020) - Hasegawa, Daiichiro; Tawa, Akio; Tomizawa, Daisuke; Watanabe, Tomoyuki; Saito, Akiko Moriya; Kudo, Kazuko; Taga, Takashi; Iwamoto, Shotaro; Shimada, Akira; Terui, Kiminori; Moritake, Hiroshi; Kinoshita, Akitoshi; et al.
Abstract: We previously reported that risk‐stratified therapy and intensive postremission chemotherapy (PRC) contributed to the improved survival of childhood acute myeloid leukemia (AML) in the AML99 study, which led us to consider a reduction in the number of PRC courses with more restrictive indications for stem cell transplantation (SCT) in the successor AML‐05 study. We here report the outcome of AML patients without core‐binding factor mutation (non‐CBF AML) in the AML‐05 study. Two‐hundred eighty‐nine children (age < 18 years old) with non‐CBF AML were eligible. Patients with unfavorable cytogenetics and/or poor bone marrow response to the first induction course were candidates for SCT in the AML‐05 study. After two courses of induction, a further three courses of PRC were given in AML‐05, while four courses were given in the AML99 study. The 3‐year event‐free survival (EFS) rate in the AML‐05 study (46.7%, 95% CI: 40.6‐52.6%) was comparable to that of non‐CBF AML in the AML99 study (51.5%, 95% CI: 42.7‐59.6%) ( P  = .16). However, the 3‐year overall survival (OS) rate in the AML‐05 study (62.9%, 95% CI: 56.3‐68.8%) was slightly lower than that in the AML99 study (71.6%, 95% CI: 63.2‐78.5%) ( P  = .060), mainly due to decreased remission induction rate and increased nonrelapsed mortality. In conclusion, reductions in the number of PRC courses from four to three, together with repetitive cycles of high‐dose cytarabine, were acceptable for non‐CBF childhood AML.